Lack of association between MTHFR A1298C variant and Alzheimer's disease: evidence from a systematic review and cumulative meta-analysis. (4th May 2017) - Liu, Shumin; Wu, Yongfu; Liu, Xu; Zhou, Jiahui; Wang, Ziyou; He, Zhiwei; Huang, Zunnan
Abstract: Objectives: Previous studies have investigated the association between MTHFR A1298C (rs1801131) polymorphism and susceptibility to Alzheimer's disease (AD). Nevertheless, an ultimate conclusion remains obscure. We then executed this meta-analysis to estimate this association more precisely. Methods: Related studies were systematically searched on PubMed, Embase, China National Knowledge Infrastructure, Google scholar, and AlzGene databases. The association was evaluated by reviewing the odds ratios (ORs) with corresponding 95% confidence intervals (CIs). Publication bias, sensitivity analysis, and cumulative meta-analysis were performed to help draw a more definite conclusion. Results: Ten eligible studies were finally enrolled in this meta-analysis. Lack of association between MTHFR A1298C polymorphism and AD risk was observed in five genetic models (allelic: OR = 1.17, 95% CI: 0.88–1.56; homozygous: OR = 1.15, 95% CI: 0.87–1.53; heterozygous: OR = 1.19, 95% CI: 0.76–1.86; dominant: OR = 1.23, 95% CI: 0.81–1.87; recessive: OR = 1.16, 95% CI: 0.89–1.52). The result of cumulative meta-analysis sorted by publication year was also detected a dynamic tendency of no correlation between MTHFR A1298C polymorphism and AD. Conclusion: This meta-analysis reveals that MTHFR A1298C polymorphism may not be associated with AD risk.